SUSTAINABLE ALKALINE MEMBRANE FUEL CELL - Raimundo, R. C.; Vargas, Jose V. C.; Balmant, W.; Ordonez, J. C.; Yang, S. (Revista de Engenharia Térmica, 2020)
This work proposes a sustainable alkaline membrane fuel cell (SAMFC) comprising a traditional AMFC coupled to a hydrogen generation reactor. The reactor uses recycled aluminum from soda cans to split the water molecule via oxidation catalyzed by NaOH, and an innovative cellulose membrane eliminates the undesirable characteristics of liquid electrolytes and asbestos or ammonia—common constituents of alkaline electrolyte membranes that are toxic and carcinogenic. Oxygen is supplied to the cell by first directing the ambient air through KOH aqueous solution to remove CO2 and thus to avoid the formation of K2CO3. In this paper, an SAMFC system with one unitary cell, reactor, and CO2 purifier was designed, built, and tested in the laboratory, and the system was compared experimentally against traditional AMFCs driven by commercial hydrogen and by the hydrogen derived from commercial aluminum. According to experimental polarization and power curves, the SAMFC delivered 0.9V in open circuit and approximately 0.42W of maximum power with recycled aluminum. The study thereby demonstrates the economic potential and competitive performance of the proposed SAMFC against traditional fuel cells.